Monomer release from resin based dental restorative materials exposed to radiation - Busra Gulec; Pinar Gul; Burak Erdemci (BMC Oral Health)
Abstract Background In patients receiving head and neck radiotherapy, ensuring and maintaining oral hygiene is very important to minimize oral complications. In order to evaluate the clinical success of restorative materials used in the treatment of dental caries, it is important to know the toxic potential of the type and amount of ions released from the restorative material as well as their mechanical properties. The aim of this study is to determine the monomer released from the materials after radiotherapy is applied to 13 different dental restorative materials based dimethacrylate resin. Methods 13 different restorative materials were used. 20 specimens were prepared from each material and specimens were randomly divided into two equal groups: experimental and control groups (n = 10). A total of 60 Gy of radiation was applied to the experimental group. During the 6-week radiotherapy procedure, the samples were kept in 75% ethanol-water solution. The monomer analysis of the collected specimens was performed using the LC-MS/MS system. The analysis of the data obtained was performed using Mann-Whitney U and Kruskal Wallis tests (α = 0.05). Results It was determined that the amount of monomer released was mostly less in the radiotherapy group than in the control group. Significant differences were found among restorative materials in terms of monomer release (p < 0.05). In terms of monomer release amounts, the highest release was from composite resin group materials, while the least was from resin ceramic materials. Conclusion Within the limits of this study, it was found that the amounts of monomer released from the investigated materials were mostly lower after radiotherapy. In addition, the amounts of monomer release were higher in the composite group materials, while the release was lower in the resin ceramics.